2014
DOI: 10.1186/2251-6581-13-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of opium addiction on thyroid function tests

Abstract: BackgroundA number of abnormalities has been identified among drug addicted users especially heroin addicts. However, there are a few studies to assess the opium effects on thyroid hormones. the aim of the present study is to investigate the effect of opium on the thyroid function tests.MethodIn this case–control, 50 male addicts, aged 20–50 years, with history of addiction to opium lasting more than two years, and 50 male non-addicts as control group were randomly selected. 10 cc blood sample was taken for me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…Findings from our current study indicate that the combined abnormality of TSH and prolactin might be one of the hormonal characteristics in obesity with food addiction rather than in general obesity. Data from a number of studies have suggested that the serum TSH level may be a marker of alcohol, opium and cocaine dependence and craving [ 51 , 52 , 53 ]. A significant negative correlation between TSH level and alcohol craving has been reported in alcohol-dependent subjects [ 51 ], and a significantly lower level of TSH has been found in opium users as compared to healthy controls [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from our current study indicate that the combined abnormality of TSH and prolactin might be one of the hormonal characteristics in obesity with food addiction rather than in general obesity. Data from a number of studies have suggested that the serum TSH level may be a marker of alcohol, opium and cocaine dependence and craving [ 51 , 52 , 53 ]. A significant negative correlation between TSH level and alcohol craving has been reported in alcohol-dependent subjects [ 51 ], and a significantly lower level of TSH has been found in opium users as compared to healthy controls [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the YFAS and Willett Food Frequency Questionnaire (FFQ) were used as tools for the diagnosis of food addiction and measuring nutrient intake over the past 12 months. These sets of measures and the criteria on which they are based have been validated in different populations [ 7 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. The YFAS is the only tool available for the diagnosis of food addiction.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of some psychoactive substances on commonly observed diseases like coronary artery disease, diabetes mellitus and some psychiatric disorders has been investigated, but effects of long-term use of these substances on endocrine system have not been studied enough ( 3 ). Studies have demonstrated controversial results about effects of psychoactive substances on hypothalamic-pituitary axis and thyroid function ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…112 However, this was not confirmed in a recent study demonstrating normal thyroid function in both opium smokers and non-addict subjects. 113 Overall, although acute opioid administration increases TSH secretion, there is accumulating evidence that chronic use is not associated with thyroid dysfunction, irrespective of dose and administration route.…”
Section: Prolactinmentioning
confidence: 99%